Developing A Flipbook for Introduction to English Grammar Course with Project-Based Learning Approach - Yosintha, Rolisda; Rekha, Agnira; Nugrahaeni, Dwitiya Ari; Maulani, Fitrotun (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
This study aimed to create a digital coursebook as a flipbook for the Introduction to English Grammar course using Project-Based Learning (PJBL). Utilizing the ADDIE model, a needs analysis was conducted to gather student preferences on language focus, learning setting, lecturer roles, and flipbook features. The resulting flipbook, consisting of 13 units, was designed to enhance students' grammatical skills for real-world communication and was validated by experts for its quality. The research emphasizes the potential of innovative, student-centered approaches in grammar education. Embedding grammar lessons into real-life scenarios through PJBL helps students recognize the practical applications of grammar and enhances retention and comprehension. The study successfully developed the flipbook in the initial phases of the ADDIE model, with future phases set to evaluate its effectiveness comprehensively. Initial findings provide valuable insights into effective grammar learning, suggesting the need for further research and development of innovative learning materials. The next phase involves piloting the flipbook in classrooms, with iterative refinements based on student feedback and outcomes to ensure it meets educational standards and student needs. This study highlights the importance of incorporating technology in educational resources to foster active learning and improve grammar proficiency among students